Pulmonary vascular alterations in explanted lung after transplantation - Demirag, Funda; Yazicioglu, Alkin; Turkkan, Sinan; Tufekcioglu, Omac; Yekeler, Erdal (Polish Journal of Pathology, 2021)
Widespread pulmonary destruction and fibrosis can be seen in end-stage pulmonary diseases. This situation causes vascular remodeling of the pulmonary circulation and pulmonary hypertension. Lung transplantation is an alternative treatment for end-stage pulmonary diseases. The purpose of this study is to research pathological vascular alterations retrospectively in explanted lungs with or without pulmonary hypertension. 57 explanted lungs were evaluated for occlusive intimal fibroelastosis, smooth muscle proliferation, medial hypertrophy, intimal cellular or fibrous thickening, hemosiderosis, plexiform lesion, angiomatoid lesion, arteriosclerosis, venopathy, capillary duplication and arteriovenous malformation. Both systolic and mean pulmonary artery pressures were defined. The relationship between vascular patterns and pulmonary hypertension was investigated. Pathological vascular alterations in explanted lungs with or without pulmonary hyper- tension included medial hypertrophy (80.71%), intimal cellular or fibrous thickening (80.7%), arteriosclerosis (77.19%), smooth muscle proliferation (55.3%) and arteriovenous malformation (50.3%). Hemosiderosis (12.5%), plexiform lesion (14%) and venopathy (21%) were less frequent pathological vascular alterations. Capillary duplication was common in secondary pulmonary hypertension and was statistically meaningful. Although medial hypertrophy and intimal thickness were seen in pulmonary hypertension, they can also be observed in end-stage pulmonary diseases without pulmonary hypertension. Interstitial capillary duplication was an important histopathological finding in end-stage lung diseases with pulmonary arterial hypertension.